Determinação da potência mecânica no limite entre os domínios pesado/severo do crawl-atado - Pessôa Filho, Dalton Müller [UNESP]; Denadai, Benedito Sérgio [UNESP] (Universidade Estadual Paulista, 2010)
The aim of this study was to access the P-tLim model in swimming, applying the load control available in full tethered swim condition. Its physiological meaning for the determination of boundary of heavy/severe domains was assessed from the relationships with critical velocity (CV), critical power (CP) and maximal lactate steady state (MLSS). The velocity at MLSS (vMLSS = 1.17 ± 0.11 m/s) and CV (1.19 ± 0.12 m/s) were significantly different. Similarly, the power at MLSS (pMFEL = 89.2 ± 15.1 W) and CP (99.4 ± 22.9 W) were significantly different. There was no difference between lactate concentration at vMLSS (3.54 ± 0.9 mM) and pMLSS (3.76 ± 0.6 mM). Significant Pearson's coefficients (r > 0.70) were observed among vMLSS and P MLSS with their respective values on time-limited model. Thus, the tethered-crawl condition seems to be valid to determine the boundary of heavy/severe domains, and to access the aerobic capacity of swimmers.

O objetivo deste estudo foi ajustar o modelo P-tLim à natação com o recurso do nado atado. Seu significado fisiológico para a descrição dos domínios pesado/severo foi obtido pelas relações com a velocidade crítica (VC), potência crítica (PC) e com máxima fase estável do lactato (MFEL). A velocidade correspondente a MFEL (vMFEL =1,17 ± 0,11 m/s) e a VC (1,19 ± 0,12 m/s) obtidas durante o nado desimpedido foram significantemente diferentes. Similarmente, a potência correspondente a MFEL (pMFEL = 89,2 ± 15,1 W) e a PC (99,4 ± 22,9 W) foram diferentes durante o nado atado. Não houve diferença da concentração de lactato na vMFEL (3,54 ± 0,9 mM) e pMFEL (3,76 ± 0,6 mM). Coeficientes de Pearson significativos (r > 0,70) foram observados entre os parâmetros vMFEL e pMFEL com seus respectivos pares do modelo tempo-limite. Assim, o nado atado parece ser válido para determinar os limites do domínio pesado/severo, podendo também ser utilizado para avaliar a capacidade aeróbia de nadadores.
Measurement of mechanical power on the boundary of heavy/severe domain in the tethered-crawl
Keywords: Front-crawl swim style; Critical power; Critical velocity; Maximal lactate steady-state; Nado crawl; Potência crítica; Velocidade crítica; Máxima fase estável do lactato